2018
DOI: 10.1371/journal.ppat.1007118
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the serine/threonine kinase StkP and the response regulator ComE controls the stress response and intracellular survival of Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is an opportunistic human bacterial pathogen that usually colonizes the upper respiratory tract, but the invasion and survival mechanism in respiratory epithelial cells remains elusive. Previously, we described that acidic stress-induced lysis (ASIL) and intracellular survival are controlled by ComE through a yet unknown activation mechanism under acidic conditions, which is independent of the ComD histidine kinase that activates this response regulator for competence development at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 88 publications
3
71
0
Order By: Relevance
“…Virus replication was allowed to progress for 24 h before infection with the S. pneumoniae R801 strain at a MOI of 30. Flow cytometry using Annexin-V-ACP/PI labeling to test necrosis/apoptosis levels revealed that a MOI of 10 of IAV led to ∼5% increase in the number of necrotic/apoptotic cells compared to non-infected cells (Fig S1A) and ∼15% after bacterial superinfection using a bacterial MOI of 30 (Fig S1B), as described [16]. In further studies, we used IAV at a MOI of 10 and S. pneumoniae at a MOI of 30 in the superinfection model.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Virus replication was allowed to progress for 24 h before infection with the S. pneumoniae R801 strain at a MOI of 30. Flow cytometry using Annexin-V-ACP/PI labeling to test necrosis/apoptosis levels revealed that a MOI of 10 of IAV led to ∼5% increase in the number of necrotic/apoptotic cells compared to non-infected cells (Fig S1A) and ∼15% after bacterial superinfection using a bacterial MOI of 30 (Fig S1B), as described [16]. In further studies, we used IAV at a MOI of 10 and S. pneumoniae at a MOI of 30 in the superinfection model.…”
Section: Resultssupporting
confidence: 56%
“…We previously demonstrated that the S. pneumoniae R801 strain can survive inside pneumocytes for several hours [16]. To further define whether a concomitant influenza virus infection would affect S. pneumoniae intracellular survival, we established an in vitro IAV- S. pneumoniae superinfection model in human-derived A549 pneumocyte cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations